Efficacy study of bio-typhoid® vaccine against fowl typhoid in backyard layer chicken (Journal of the Bangladesh Agricultural University, 2010)
The study was performed with a view to isolate and identify a virulent strain of S. gallinarum and determine the purity, safety and efficacy of BIO-TYPHOID® vaccine. A total of 40 backyard layer chicken were used for this study where Group A was used for experimental vaccination, Group B kept as control and Group C was used for calculating virulent S. gallinarum challenge dose. Primary and secondary vaccination was carried out at 40 days and 110 days of age, respectively. Blood samples were collected to obtain the sera after vaccination from both vaccinated and unvaccinated control group and antibody titres were determined by Microplate agglutination test. The antibody titre increased in primary vaccination up to days 56 days post vaccination (DPV) and then decreased gradually. The highest antibody titre (Mean ± SE) 384.00 ± 42.67 was obtained at 91 DPV (21 days later of secondary vaccination) and maintained up to 98 DPV. Safety test was done by inoculating mice and purity test of the vaccine was done by inoculating on to Blood Agar media. The efficacy of BIO-TYPHOID® vaccine was recorded as 90% which was determined by challenge infection with 0.1 ml of 5x105 CFU virulent S. gallinarum. Results of this study revealed successful protections by BIO-TYPHOID® vaccine. Keywords: BIO-TYPHOID® vaccine; Chicken; Efficacy; Fowl Typhoid DOI: 10.3329/jbau.v7i2.4737 J. Bangladesh Agril. Univ. 7(2): 295-299, 2009